Australian Airports and Local Economic Development. Issue 1 (1st January 2023) - Ke, Meihong; Baker, Douglas
ABSTRACT: This article investigates the impact of airports on the surrounding landside industrial development by employing secondary data of nine major Australian airports captured from Google Maps using MapQuery . Previous studies suggest a strong connection between airports and economic development at the regional scale. However, few studies explore this link around the surrounding vicinity of the airport. This article provides new evidence on the link between airports and the local economy in the Australian context. The empirical results demonstrate that the size of landside industries is highly correlated with both airports' passenger numbers and international air freight volume at the correlation coefficient of 0.912 and 0.871. Service sectors account for over 50 percent in the landside industries of most airports indicating a tendency of diversified and service-oriented landside development, which implies that airports are drivers of economic restructuring. The evidence confirms that airports have a positive impact on landside industrial development around airports, which align with the findings within this strand of airport literature.